2013
DOI: 10.1634/theoncologist.2013-0193
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia With Endocrine Therapies in Patients With Cancer

Abstract: Learning Objectives Define the incidence and grades of alopecia to endocrine‐based therapies in cancer patients. Differentiate risk of alopecia to various endocrine agents used against cancer. Design therapeutic, counseling, and supportive care strategies for patients requiring endocrine agents causing alopecia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 59 publications
0
39
0
1
Order By: Relevance
“…[35] Indirect evidence for a protective effect of oestrogens on human hair growth comes from the increasing prevalence of FPHL following the menopause, the prolongation of anagen during pregnancy [36] and reports of hair loss in women taking tamoxifen or aromatase inhibitors for the treatment of breast cancer. [37] One study found lower oestrogen/androgen ratios in premenopausal women with FPHL compared to a control group, suggesting a protective effect of oestrogen on hair loss, although the number of subjects was quite small. [38] Interestingly, androgen levels were slightly lower in the FPHL subjects than in controls although the difference was not significant.…”
Section: Sex Steroid Hormonesmentioning
confidence: 99%
“…[35] Indirect evidence for a protective effect of oestrogens on human hair growth comes from the increasing prevalence of FPHL following the menopause, the prolongation of anagen during pregnancy [36] and reports of hair loss in women taking tamoxifen or aromatase inhibitors for the treatment of breast cancer. [37] One study found lower oestrogen/androgen ratios in premenopausal women with FPHL compared to a control group, suggesting a protective effect of oestrogen on hair loss, although the number of subjects was quite small. [38] Interestingly, androgen levels were slightly lower in the FPHL subjects than in controls although the difference was not significant.…”
Section: Sex Steroid Hormonesmentioning
confidence: 99%
“…While more than half of women with breast cancer report alopecia as the most traumatic adverse event during treatment, hormone therapy-induced alopecia (HTIA) is still largely underreported, with only 6% of studies of tamoxifen reporting it [ 60 ]. In a meta-analysis of 35 studies ( n = 13,415 patients) the incidence of all-grade HTIA ranged from 0% with anti-androgen therapies to 25% with selective estrogen receptor modulators (SERMs), corresponding to an overall incidence of 4.4% [ 60 ]. In a retrospective study of the data for 112 patients treated with SERMs/aromatase inhibitors, HTIA was most often (92%) characterized by an androgenic alopecia pattern and low severity grade [ 61 ].…”
Section: Hair Toxicitiesmentioning
confidence: 99%
“…appear to play a role [115, 116]. It must be noted that the long-term (2–10 years) adjuvant endocrine-based anticancer therapies (antioestrogens and aromatase inhibitors) may also cause and/or exacerbate hair loss [120]. …”
Section: Hair and Nail Changesmentioning
confidence: 99%